Certain aspects of analysis of automated and workshop programming of NC machine tools - Gatalo, Ratko; Hodolič, Janko; Zeljković, Željko; Živanović, Miloje (Journal of Production Engineering, 1993)
In this paper, an analysis is conducted on some of the methods and systems of NC part programming that are in use at the Institute for Production Engineering. The paper begins with a general discussion of the approaches and methods for programming NC machine tools. Programming is classified based on location into workshop (on-line) and external (off-line) programming. The paper then proceeds to present various workshop programming methods. It includes a case study involving the machining of a family of similar parts, with program solutions derived from the following programming methods: "point-to-point" programming, programming using "fixed cycles," and parameterized programming. The third part of the paper explores three systems for automated programming, each operating at a different level of automation: INDEX System H200, I-DEAS GNC system, and SAPOR-S system. SAPOR-S, an original solution developed at the Institute for Production Engineering, is detailed. The analysis of these systems is complemented by samples of their source code for a specific part. The final section of the paper presents a comparative analysis of the reviewed programming methods. It provides separate comparisons, first between workshop and then between automated programming methods. The paper concludes with a summary of the results of the comparative analysis of all the considered methods and outlines directions for future research.